2015
DOI: 10.20884/1.mib.2015.32.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Kualitas Air Sungai Condong yang terkena Buangan Limbah Cair Industri Batik Trusmi Cirebon

Abstract: The aims of this study were to assess the water quality of the River Condong and Condong River Quality Statebased on physical, chemical and biological parameters. Sampling was carried out in seven stations with 3 repetitions at intervals of one month. Water quality were analyzed descriptively by reference raw Water Quality Standard.  Determination of the stateof water quality using methods Storet. Results of laboratory tests showed that the water quality of the River Condong exceed the Water Quality Standard G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
5
0
4
Order By: Relevance
“…These anthropogenic activities affected the DO, ammonia, and phosphate parameters to negatively increase the STORET score (-20) -(-30). These results were in line with the previous study on the STORET index of -31 in Condong River (Cirebon District) (Supenah et al, 2015).…”
Section: Analyses Of Storet and Pollutant Indexsupporting
confidence: 93%
See 1 more Smart Citation
“…These anthropogenic activities affected the DO, ammonia, and phosphate parameters to negatively increase the STORET score (-20) -(-30). These results were in line with the previous study on the STORET index of -31 in Condong River (Cirebon District) (Supenah et al, 2015).…”
Section: Analyses Of Storet and Pollutant Indexsupporting
confidence: 93%
“…Based on these methods, the US-EPA framework classifies the water quality into four classes (Saraswati, Sunyoto, Kironoto, & Hadisusanto, 2014). Supenah, Widiastuti, and Priyono (2015) have studied the water quality of the Condong river in Cirebon using the STORET index. The study showed that the wastewater effluent from the textile and garment industrial area (Batik) heavily contaminated the river.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai sulfida dalam kurun waktu 3 periode pengamatan yaitu tahun 2016, 2018, dan 2019 tidak memenuhi baku mutu kelas I. Fenomena keberadaan senyawa yang melebihi baku mutu kelas I diasumsikan karena buangan air limbah tanpa pengolahan terlebih dahulu ke Sungai Bedadung dari industri tekstil dan laundry. Berdasarkan kajian lainnya yang dilakukan oleh Supenah et al (2015), menjelaskan bahwa pembuangan zat warna dari pencucian berpotensi meningkatkan nilai sulfida pada Sungai Condong Kabupaten Cirebon.…”
Section: Perhitungan Indeks Kualitas Airunclassified
“…The construction of factories around the watershed (DAS) causes pollution of the aquatic environment, especially due to contamination of industrial waste in the form of heavy metals. Heavy metals that are often disposed of with industrial waste and will become polluting agents in the environment include: Lead (Pb), Mercury (Hg), Cadmium (Cd), Arsenic (As), and so on (Supenah, et. al., 2015).…”
Section: Introductionmentioning
confidence: 99%